12-month outcomes of the US patient cohort in the SONATA pivotal IDE trial of transcervical ablation of uterine fibroids - Hudgens J; Johns DA; Lukes AS; Forstein DA; Delvadia D (Dove Medical Press, 2019)
Joseph Hudgens,1 D Alan Johns,2 Andrea S Lukes,3 David A Forstein,4 Dipak Delvadia51Department of Obstetrics and Gynecology, Eastern Virginia Medical School, Norfolk, VA, USA; 2Baylor Research Institute-Fort Worth, Fort Worth, TX, USA; 3Carolina Women’s Research and Wellness Center, Durham, NC, USA; 4Department of Obstetrics and Gynecology, Touro College of Osteopathic Medicine, New York, NY, USA; 5Department of Obstetrics and Gynecology, Drexel University College of Medicine, Philadelphia, PA, USAObjective: The prospective SONATA pivotal Investigational Device Exemption (IDE) trial was performed in the United States (US) and Mexico to examine the safety and effectiveness of transcervical fibroid ablation (TFA) in the treatment of symptomatic uterine fibroids. This is an analysis of 12-month clinical outcomes in the US cohort.Methods: TFA with the Sonata® System was performed on women with symptomatic uterine fibroids. The 12-month co-primary endpoints were reduction in menstrual blood loss and freedom from surgical reintervention. Symptom severity, quality of life, patient satisfaction, safety, and reductions in uterine and fibroid volumes were also evaluated.Results: One hundred twenty-five patients were enrolled and treated in the US. Both co-primary endpoints were achieved in this US-based cohort, as 65.3% of patients reported ≥50% reduction in menstrual bleeding and 99.2% of patients were free from surgical reintervention. Symptom improvement was noted by 97.4% of patients and 98.3% were satisfied. Ninety-five percent of patients reported reduced menstrual bleeding at 12 months, and 86.8% noted >20% reduction. Significant mean improvements at 12 months were realized in both symptom severity and health-related quality of life (33.8 points and 45.8 points, respectively; all P<0.0001). Mean maximal fibroid volume reduction per patient was 63.8%. There was a 0% incidence of device related adverse events. Mean length of stay was 2.5 hrs and 50% of patients returned to normal activity within 1 day.Conclusion: This analysis of US patients in the SONATA pivotal IDE trial demonstrates results consistent with those in the full cohort. TFA with Sonata significantly reduced fibroid symptoms with a low surgical reintervention rate through 12 months. These results support the efficacy and safety of the Sonata system as a first-line treatment for women affected by symptomatic uterine fibroids.Keywords: uterine leiomyoma, transcervical fibroid ablation; TFA, radiofrequency ablation, Sonata system